Evaluation of alginate hydrogel encapsulated mesenchymal stem cell migration in horses - Santos, Vitor Hugo Dos [UNESP]; Pfeifer, João Pedro Hübbe [UNESP]; Souza, Jaqueline Brandão De [UNESP]; Stievani, Fernanda De Castro [UNESP]; Hussni, Carlos Alberto [UNESP]; Golim, Marjorie de Assis [UNESP]; Deffune, Elenice [UNESP]; Alves, Ana Liz Garcia [UNESP] (Elsevier, 2019)
Osteoarthritis is an incapacitating disease characterized by pain and a progressive decrease in joint mobility. The implantation of mesenchymal stem cells (MSCs) has shown promising results for its treatment. The challenge remains to keep the cells longer at the site of action, increasing their therapeutic potential. The aim of this study was to evaluate the effectiveness of the Qtracker® 655 nanocrystal marking on allogeneic synovial membrane (SM) MSCs, encapsulated in alginate hydrogel, evaluating the migration of these cells. The 10 radiocarpal joints were submitted to arthroscopic surgery (D0), divided into two groups. The chondral defect was treated according to the group: GA free-labelled MSC SM and GB labelled MSC SM microcapsules. Seven days after lesion induction and implantation of labelled cells, biopsies of the lesion site were performed in two animals, and fragments of SM and joint capsule also collected, which were frozen and later processed for fluorescence microscopy. The synovial fluid of the three animals was analyzed by flow cytometry three times – 3, 7 and 21 days after application. The cellular marking with the nanocrystals allowed the visualization of the cells in cartilage, synovial membrane, synovial fluid and articular capsule, but with a predilection for the synovial membrane and the lesion site was scarce. The labelled MSC SM in microcapsules were scarce in the synovial fluid and could be related to the small quantity of MSCs leaving the pores of the microcapsules, also favorable results, as the cells release paracrine effects acting for a long period until the cellular differentiation.
Keywords: Cartilage; Horse; Quantum dots; Scaffold; Tissue engineering; Tracking